2006
DOI: 10.1086/509502
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Star Formation in Compact Groups of Galaxies: A Stellar Population Study

Abstract: We present the results of a study comparing the stellar populations in the elliptical galaxies of Hickson compact groups ( HCGs) with those in low-density environments. We analyze a sample of intermediate-resolution (4.25 8 FWHM ) spectra of 22 galaxies in HCGs and 12 in the field or in loose groups. Three different population-synthesis models and stellar population analyses are used to make the results more robust. Great care has been taken to correct for the emission contamination of the Balmer lines, used t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
48
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 63 publications
(126 reference statements)
11
48
2
Order By: Relevance
“…Stars from galaxies in compact groups. De la Rosa et al (2007) have found that galaxies with σ 0 160 km s −1 in Hickson Compact Groups have larger [Mg/Fe] and lower [Z/H] compared to field galaxies of similar masses, and proposed that such galaxies may have their otherwise extended star formation quenched by mergers. 3.…”
Section: The Extended Symmetric Halomentioning
confidence: 99%
“…Stars from galaxies in compact groups. De la Rosa et al (2007) have found that galaxies with σ 0 160 km s −1 in Hickson Compact Groups have larger [Mg/Fe] and lower [Z/H] compared to field galaxies of similar masses, and proposed that such galaxies may have their otherwise extended star formation quenched by mergers. 3.…”
Section: The Extended Symmetric Halomentioning
confidence: 99%
“…In the low metallicity regime, however, our models combine scaled-solar isochrones with stellar spectra that do not show this abundance ratio pattern (e.g., Edvardsson et al 1993;Schiavon 2007). However our (base) models, can be used to obtain a good proxy for the [Mg/Fe] abundance ratio, if appropriate line indices are employed (Yamada et al 2006;de la Rosa et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using Lick indices to determine the stellar population contents of elliptical galaxies in small samples of HCG have shown that the formation process of these galaxies is similar to that of ellipticals in clusters of galaxies (Proctor et al 2004;Mendes de Oliveira et al 2005;de la Rosa et al 2007), and suggested that their formation took place at least 2 Gyr in the past. This is already older than predicted by the fast merger scenario for CG, which has led some authors (e.g., Proctor et al 2004;Mendes de Oliveira et al 2005) to propose that CG are defying the standard cosmological model of structure formation.…”
Section: Introductionmentioning
confidence: 99%